The Possibility Prediction of Inheriting Blood Types in Parents Based on The Child's Allele Combination - Mochamad Fabian, Reyhan; Adi Nugroho, Afrizal; Salsa Billa, Aidha; Munawir, Munawir; Taufik Dwi Putra , Muhammad (Information Technology International Journal, 2024)
The application of predicting the likelihood of blood group inheritance in children based on allele combinations from parents is becoming increasingly relevant. Understanding the combination of alleles that may appear in offspring can provide better insight for individuals and couples in planning families. The existence of an application to predict a child's blood type by using program development to form a family tree based on blood type can provide a clear visual picture of the inheritance of blood type from generation to generation. The purpose of this research is to identify allelic combinations of certain genes that affect a person's blood type and analyze how genetic inheritance occurs from parents to children. This study proves that we can see the likelihood of blood type inheritance of a child by looking at the allele combinations of both parents. This concept can be explained using the concept of a family tree (Tree). By using the Tree concept, we can easily visualize the inheritance of blood groups based on alleles, and facilitate the understanding of the formation of allele combinations that occur in the genetic inheritance process.